Estimation of carbon nanotubes and their applications as reinforcing composite materials–An engineering review. (15th September 2021) - Garg, A.; Chalak, H.D.; Belarbi, M-O.; Zenkour, A.M.; Sahoo, R.
Abstract: The demand for increasing the strength of the structural element without an increase in the size of the elements leads to the introduction of reinforcements. Employing carbon nanotubes for increasing the strength of the material has been successfully carried out in the last decade of the twentieth century. In the present work, a review has been carried regarding predicting material properties of single-walled carbon nanotubes (SWCNTs) using computational models. Different approaches related to predicting the properties are discussed in detail. Also, the present work summarizes the review on the analysis of SWCNT reinforced composite beams, plates, and shells under static, vibration, and buckling conditions. After the detailed review, gap areas are also reported in the present work which will help in the research work to be carried out in near future on the related topic.